T-cell exhaustion in COVID-19: what do we know? - Chen-Camaño, Roderick; DeAntonio, Rodrigo; López-Vergès, Sandra (Frontiers in Immunology, 2025)
T-cell exhaustion is a terminal state of immune dysfunction characterized by impaired proliferation and effector functions, diminished cytokine secretion, and sustained expression of inhibitory receptors. In coronavirus disease 2019 (COVID-19), increasing evidence links exhausted T-cell phenotypes with poor clinical outcomes, including severe disease, delayed viral clearance, and persistent symptoms associated with Long COVID. Exhaustion results from prolonged antigenic stimulation and inflammatory signals and is marked by transcriptional reprogramming, metabolic and epigenetic dysregulation, and co-expression of inhibitory receptors such as programmed cell death protein-1 (PD-1), T-cell immunoglobulin and mucin-domain containing-3 (TIM-3), and cytotoxic T-lymphocyte-associated protein 4 (CTLA-4). Notably, exhausted phenotypes in COVID-19 frequently coexist with hyperactivation, raising the unresolved question of whether inhibitory receptor expression reflects transient activation or irreversible dysfunction. Emerging therapeutic strategies to reverse these dysfunctional states include immune checkpoint inhibitors, cytokine modulation, metabolic interventions, and epigenetic therapies, although their clinical translation remains at an early stage. Critical research gaps include the scarcity of longitudinal data, incomplete profiling of T-cell subsets across disease stages during COVID-19 and Long COVID-19, and contradictory evidence of vaccine-induced exhaustion with limited understanding of its consequences. This non-systematic literature review synthesizes current advances in COVID-19 immunopathology and therapeutic strategies, underscoring that understanding T-cell exhaustion is crucial to improving outcomes and shaping next-generation immunotherapies and vaccines.